Ulsterczyk o imieniu Achilles - Schade, Gerson (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2019)
Schade Gerson, An Ulsterman Named Achilles (Ulsterczyk o imieniu Achilles). A new novel by an English-writing author turns out to be a careful reworking of the story of Achilles, as it is told by Homer. The article elucidates how the modern text works and suggests how it may relate to an ‘Irish’ gaze. A new term, décalage, is introduced to describe a particular poetic device that belongs to the many ways of establishing intertextuality.